Rare DICER1 and Absent FOXL2 Mutations Characterize Ovarian Juvenile Granulosa Cell Tumors. (February 2021) - Baillard, Pauline; Genestie, Catherine; Croce, Sabrina; Descotes, Françoise; Rouleau, Etienne; Treilleux, Isabelle; Gouy, Sebastien; Morice, Philippe; Ray-Coquard, Isabelle; McCluggage, W. Glenn; Devouassoux-Shisheboran, Mojgan
Abstract : FOXL2 somatic mutation occurs in a high percentage of ovarian adult granulosa cell tumors and DICER1 mutations in a high proportion of Sertoli-Leydig cell tumors. These mutations have only been studied in a limited number of juvenile granulosa cell tumors (JGCTs), and their occurrence and frequency in these neoplasms is controversial. We aimed to determine the frequency of FOXL2 and DICER1 mutations in a large cohort of 50 JGCTs, and to evaluate the prognostic impact of these mutations. A FOXL2 hotspot mutation was found in 2/50 JGCTs. Review of these 2 cases reclassified them as adult granulosa cell tumors. Thus, FOXL2 mutation was absent from our large cohort of JGCTs. DICER1 mutations in the RNase IIIb domain were found in 4 cases. After review of the mutated cases, 1 was reclassified as a gynandroblastoma with a prominent JGCT component. Thus, DICER1 mutations were detected in 3/47 (6%) of pathologically confirmed JGCTs. Our results show that FOXL2 mutations are not present in JGCT, whereas a small percentage of these neoplasms exhibit DICER1 mutations.